THE EFFECT OF INDIVIDUAL MORALITY AND INTERNAL CONTROL SYSTEM SAGAINST FRAUD AT THE PUBLICSERVICE CENTER IN PINRANG REGENCY - Hernianti Harun; Irwan Irwan (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis, 2022)
This study aims to obtain evidence of the individual morality effect in committing acts of accounting fraud (fraud) and to obtain evidence of the effect of the internal control system in committing acts of accounting fraud (fraud). The data collection technique used in this study was a questionnaire. The sample in this study amounted to 87 respondents. The analysis used in this study was multiple linear regression. The results in this study indicate that individual morality had a negative and significant effect on fraud. This means that the bad individual morality, the higher the level of accounting fraud. Furthermore, the internal control system had a negative and significant effect on fraud. This means that the bad internal control system, the higher the level of accounting fraud.